Islamic Education Management's Response to the Challenges of Globalization and the Era of Disruption: An Analysis of Sustainable Strategies in Malaysia - Rodrigue Fontaine (Samarinda International Journal of Islamic Studies (SIJIS), 2026)
The rapid advancement of globalization and digital disruption presents a dual challenge for Islamic educational institutions: maintaining traditional religious values while achieving global competitiveness. Malaysia has emerged as a significant model in navigating this tension through strategic institutional reforms. Objective: This study aims to analyze the strategic responses of Islamic education management in Malaysia to globalization and the era of disruption, focusing on the sustainability of these strategies. Methods: Utilizing a qualitative descriptive-analytical approach, this research synthesizes official policy documents (e.g., Malaysia Education Blueprint 2025) and academic literature from 2021–2025 via a Systematic Literature Review (SLR) framework. Results: The findings reveal that Malaysia’s management response is characterized by "Maqasid-based Strategic Management," which integrates digital transformation (Smart Madrasahs), international quality accreditation, and financial autonomy through productive waqf. Contrary to fears of secularization, digital tools have catalyzed a "re-spiritualization" of education, enhancing the accessibility and personalization of religious learning. Conclusion: Sustainable strategies in Malaysia succeed by anchoring modern technological efficiency in traditional Islamic ethics (Adab). This SIEM (Sustainable Islamic Education Management) model offers a viable roadmap for other Muslim-majority nations to achieve educational modernization without identity loss.